Relationship between National Interest and Global Interest in Foreign Policy of a State - Onyemekihian , Jude; Onyekwuma, Ebie Sunday (Social Science Research, 2022)
International socialization has undeniably reshaped international relations. Similarly, the internationalization of national interests and national politics cannot be discounted. The national and global interests are readily distinct notions since both elements play a key role in developing external policy. Thus this paper examined the relationship between national interest and global interest in the foreign policy of a State. The study will take an all encompassing view of national interest and foreign approach. It will examine a state’s national interest and her Afro centric foreign policy. Consideration will be paid to those techniques put in place for the accomplishment of a state’s national interest. The paper utilized secondary data sourced from the internet, journals, magazines, newspapers and the internet. The paper argued vehemently that foreign policy is "primarily generated within states and that the influence of global interest forms the basis of national interest, overshadowing but not discounting the remaining elements. The paper concluded that the correlation between national and global interest areas is of great strength.